Prevalence and Risk Factors Associated with Malnutrition among Children with Learning Disabilities: A Scoping Review - Hashim, Nur Hamiza Ruzaini; Harith, Sakinah; Bakar, Raishan Shafini; Sahran, Nur-Fazimah (2017)
Introduction: By the end of 2015, about 72,152 children with learning disabilities were registered under the Malaysian Welfare Service Department (JKM). Malnutrition has been found to be a common setback among children with learning disability (LD). This study presents available evidence on the prevalence and risk factors associated with malnutrition in children with LD. Methods: A framework suggested by Arksey & O`Male (2005) was used to carry out this scoping review. Published articles, reviews and reports were identified through a complete search. Inclusion criteria for the search were English articles related to LD, published from 2005 to 2016. Results: Seventeen international studies published from 2005 until 2015 with a total of 318,596 participants and one study involving 281 participants from Malaysia, were identified and included in this review (n=18). The target age range of the sample in these 18 studies was 2 - 20 years, with a mean age of 3.2 - 14.2 years. The prevalence of underweight among children with LD was 3.4 - 36%, overweight 7.6 - 37% and obesity 5.7 - 52%. Several studies reveal that malnutrition risk among children with LD is significantly associated with gender, age, genetic syndrome, type of disability, medication used, and country economic status. Conclusion: A number of studies show that children with LD have a higher prevalence of being overweight and obese than typically developing children and the risk associated with obesity significantly increases with age.